Signifikansi Analisis Elenktik Bagi Metode Studi Agama di Perguruan Tinggi Agama Islam (PTAI) - Ustadi Hamsah (UIN Sunan Kalijaga Yogyakarta, 2016)
In the context of modern science, Religious Studies is a branch of science that has been emerged in the “structure of plausibility” of Western traditions. As a scientific knowledge, Religious Studies differs from Theology and Philosophy in which scholars, like Friedrich Max Müller, applied the scientific and empirical method in their research. In this regard, Religious Studies would be a part of “positivistic sciences”. In applying those scientific approaches and methods at the Islamic Studies which has been held in Islamic universities like UIN, IAIN, and STAIN, and other high educations in Indonesia will cause epistemological and axiological problem. Inter-relationship between subject and object is a main obstacle of this discipline. The method of Western sciences is constructed by empirical approach an sich while Islamic scientific tradition reflected by conviction which proved by empirical approach known as sui generis cum doctriner method. According to that problem, by applying Karl Manheim’s ‘structure of plausibility’ and Foucault’s ‘archaeology of knowledge’, this article attempts to explore the roots of epistemology of Religious Studies in Islamic higher education institution. Furthermore, this article also attempts to introduce the analysis model of Religious Studies in the Islamic institution namely elenctic method. This method assumes that religious phenomena can be analyzed by two phases, firstly by describing all of religious phenomena as what is understood by its adherents, and secondly by analyzing those religious phenomena with theoretical approaches.[Studi Agama, dalam konteks keilmuan modern, merupakan cabang ilmu yang lahir dalam structure of plausibility budaya dan tradisi Eropa. Epistemologi yang dibangun berlandaskan millieu tradisi Eropa meskipun Studi Agama merupakan ilmu pengetahuan yang berasaskan metode ilmiah yang berbeda dengan Teologi dan Filsafat. Pendekatan ilmiah modern yang dijadikan standar keilmuan Studi Agama dipandang akan membawa ilmu ini pada ilmu yang positive. Hal yang paling mendasar yang menjadi persoalan adalah hubungan subjek dan objek dalam ilmu pengetahuan. Persoalan ini akan sangat terasa ketika Studi Agama diaplikasikan dalam konteks Islamic Studies di Perguruan Tinggi Agama Islam (PTAI), seperti UIN, IAIN, PTAIN, dan perguruan tinggi Islam lainnya. Ilmu di Barat dibangun atas dasar ilmiah murni, sedangkan di dunia Islam ilmu merupakan refleksi keyakinan dengan pembuktian secara empirik (sui generis cum doctriner). Berdasarkan pembacaan seperti ini, dengan mengaplikasikan teori structure of plausibility dari Karl Manheim dan archaeology of knowledge dari Michel Foucault, artikel berikut akan menggali akar epistemologi Studi Agama. Kemudian di dalam artikel ini juga akan diperkenalkan sebuah cara pandang untuk menganalisis unit-unit pada disiplin Studi Agama khususnya di PTAI, yakni metode elenktik. Metode ini diaplikasikan dalam dua tahap, pertama dengan mendeskribsikan seluruh fenomena keagamaan sebagaimana diyakini oleh pemeluknya, dan yang kedua dengan menganalisisnya dengan berbagai pendekatan keilmuan secara ilmiah.]